Innovations to Serve Low-Income Citizens: When Corporations Leave Their Comfort Zones. Issue 3 (June 2016) - Gutiérrez, Roberto; Vernis, Alfred
Abstract : Some companies succeed in developing a business that serves the poor at the "base of the pyramid" (BOP), while others do not go beyond pilot programs. Understanding the reasons behind these performances is important because of their significant differences in social impact. The former create economic value by developing full-fledged business units that generate considerable social value; many firms, among the latter, choose to avoid the challenge of integrating social ventures in their businesses. We undertook a detailed comparative study of the internal and external conditions surrounding two multinational utilities that distribute natural gas. The extremely different outcomes we found highlight the need for a pressing role by civil society organizations and adequate government interventions to increase access to basic services. In monopoly sectors, such pressure is only equated by considerable increases in the level of earnings to be successful in making firms leave their "comfort zones" and deliver on the BOP promise.